PROFITABILITAS, DAN UKURAN PERUSAHAAN SEBAGAI FAKTOR PENENTU LEVERAGE PERUSAHAAN DI INDONESIA - Vio Loren Qusibah; Irdha Yusra (JURNAL PUNDI, 2019)
The study conducted to enhance the knowledge about the influence of profitability and firm size to the Leverage. The population is all companies which are listed in Indonesia Stock Exchange in 2013-2017 periods. The sample collection technique has been carried out by using purposive sampling method and based on the predetermined criteria, 114 companies have been selected as samples. The data of the financial statement of the companies has been obtained from the official website of IDX. The analytical method used is regression analysis of panel data. The study show that profitability and firm size have negative and significant influence on leverage in Indonesia